Ship stability for masters and mates - Barrass, C. B. (Elsevier / BH, 2012)
Understanding ship stability - the ability of a ship to return to an initial state after disturbing forces and moments - is critical for all maritime students and professionals studying for a deck or engineering certificate of competency, or seeking promotion to a higher rank within marine or naval companies or institutions. The seventh edition of this classic text provides a comprehensive introduction to all aspects of ship stability and ship strength, squat, interaction and trim, materials stresses and forces, with numerous worked examples to assist masters, mates and engineering office.
Keywords: Stability of ships.; Naval architecture.; elektronické knihy; electronic books